2013
DOI: 10.1016/j.jcma.2012.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal analysis of nociception-related spinal cord matrix metalloproteinase expression in a murine neuropathic pain model

Abstract: Expression of several nociception-related MMPs was differentially regulated both temporally and spatially following nerve injury. These results suggest that neuronal remodeling requires concerted expression of particular MMPs in specific temporal and spatial patterns, which may be necessary for neuronal plasticity and/or recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 44 publications
1
14
0
2
Order By: Relevance
“…Furthermore, intrathecal injection of MMP-2 caused neuropathic pain in mice, whilst peritoneal administration of GM6001, a general inhibitor of MMP, significantly attenuated thermal hyperalgesia and tactile allodynia induced by nerve injury. 23 Therefore, both MMP-9 and MMP-2 seem essential for the development and maintenance of chronic neuropathic pain, as these metalloproteinases are involved specifically in the initiation and the persistence of neuropathic pain, respectively.…”
Section: Matrix Metalloproteinase and Microglia Interactionmentioning
confidence: 99%
“…Furthermore, intrathecal injection of MMP-2 caused neuropathic pain in mice, whilst peritoneal administration of GM6001, a general inhibitor of MMP, significantly attenuated thermal hyperalgesia and tactile allodynia induced by nerve injury. 23 Therefore, both MMP-9 and MMP-2 seem essential for the development and maintenance of chronic neuropathic pain, as these metalloproteinases are involved specifically in the initiation and the persistence of neuropathic pain, respectively.…”
Section: Matrix Metalloproteinase and Microglia Interactionmentioning
confidence: 99%
“…In the next step, pro-inflammatory compounds such as metalloproteinases are produced, enzymes inducing connective tissue around nerves to expand and to become hyperactivated. 4 These initial steps are followed by activation of a number of pro-inflammatory cells, such as mast cells, macrophages, fibroblasts, neutrophils, and Schwann cells. 5 This leads to a release of various pro-inflammatory molecules: ATP, cytokines, CCL2, PGs, and various NGFs.…”
Section: Pathogenesis In Nerve Compression Syndromesmentioning
confidence: 99%
“…It suggests these proteolytic enzymes play a role in NP pathomechanism . Other studies conducted on animal models demonstrated rise in MMP‐2 and MMP‐9 activities in different phases of NP development . MMP‐9 showed rapid but short‐lasting upregulation (1–3 days) in the primary sensory neurons in the dorsal roots ganglions (DRG) after spinal nerve ligation in mice.…”
Section: Introductionmentioning
confidence: 99%
“…Different mechanisms of NP may contribute to a single disease entity in one patient and may be responsible for diversity of clinical manifestations . Studies on animal models demonstrated a role of metalloproteinases (MMPs), particularly MMP‐2 and MMP‐9, in pathomechanism of NP . MMPs act not only as mediators for neuroinflammation but may also be directly involved in evoking pain associated with nerve damage .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation